Microencapsulation of Anthocyanin Extract from Roselle (Hibiscus sabdariffa L.) Calyx using the Spray Drying Method - Halim, Yuniwaty; Erika, Erika; Natania, Natania; Handayani, Ratna (Department of Technology of Agricultural product (THP) Jambi University, 2025)
Roselle (Hibiscus sabdariffa L.) is one of the plants that is rich in anthocyanins. Anthocyanin pigments are usually unstable; therefore, one method to increase their stability is microencapsulation using various coating agents. This research aimed to determine the optimal ratio of maltodextrin and whey protein isolate (WPI) as a coating agent for producing roselle extract microcapsules and to assess the effects of pH and temperature on microcapsule stability. Dried roselle calyx was initially extracted using combinations of ethanol, distilled water, and citric acid. The roselle extract had a yield of 73.48%, a moisture content of 39.44%, a pH of 2.53, a total anthocyanin content of 38.85 mg/L, and a color intensity with a wavelength peak at 522 nm and an absorbance of 2.414. The roselle extract was then encapsulated using maltodextrin and whey protein isolate as coating agents at different ratios (1:0, 1:3, 1:1, 3:1, and 1:0) using the spray drying method. The chosen ratio of maltodextrin and whey protein isolate was 1:0, with color intensity (absorbance at 520 nm) of 0.453±0.01, yield of 66.60±4.04%, moisture content of 11.04 ±0.56%, solubility of 81.40 ±5.39%, total anthocyanin content of 10.33 ±0.25 mg/L, and encapsulation efficiency of 92.12 ±2.63%. Furthermore, the stability of the selected microcapsules at different pH (2, 4, 6, 8, and 10) and temperatures (25°C, 40°C, 55°C, 70°C, and 85°C) was assessed based on total anthocyanin content and color intensity. Results showed that the highest stability of roselle extract microcapsules was obtained at pH 2-6 and temperature below 70°C.